Necessary Stability Conditions for Linear Difference Equations in Continuous Time - Campos, Emanuel Rocha; Mondie, Sabine; Di Loreto, Michael (IEEE transactions on automatic control, 2018)
A study on the stability of continuous-time difference equations is presented. Based on the construction of the analogous of the delay Lyapunov matrix for this class of equations, a complete type Lyapunov-Krasovskii functional is proposed, that allows to present necessary stability conditions. Examples are given throughout the paper to illustrate these conditions.